Sistem Infomasi Sekolah SMPN 13 Kupang - Fridson Ever Lailena; Djoni Haryadi Setiabudi (Jurnal Infra, 2019)
School is the main source of learning for every child that they must attend in order to grow up. Therefore schools also have full responsibility in giving attention to their students. This must also be supported by parents who are active in every child's development in school. But sometimes parents don't get important information about their child because of the limited means of delivering information. To solve this problem, the final design and implementation of information systems using internet technology was made in this final project. Thus parents and students can more easily access information from schools such as grades, schedules, etc.Designing applications is done on a web basis. Every process that occurs in the system is described by DFD and ERD. After each process has been formed, the program is implemented into the PHP programming language and MySQL Server database. After implementation, the different features include admin modules, principals, students and parents / guardians, and teachers.The information system that has been created can be used to convey information from the school to parents both academic information concerning grades, lesson schedules, and other information.